Natural products for the treatment of chemotherapy-related cognitive impairment and prospects of nose-to-brain drug delivery - He, Yu-Qiong; Zhou, Can-Can; Jiang, Sheng-Gui; Lan, Wen-Qian; Zhang, Feng; Tao, Xia; Chen, Wan-Sheng (Frontiers in Pharmacology, 2024)
Chemotherapy-related cognitive deficits (CRCI) as one of the common adverse drug reactions during chemotherapy that manifest as memory, attention, and executive function impairments. However, there are still no effective pharmacological therapies for the treatment of CRCI. Natural compounds have always inspired drug development and numerous natural products have shown potential therapeutic effects on CRCI. Nevertheless, improving the brain targeting of natural compounds in the treatment of CRCI is still a problem to be overcome at present and in the future. Accumulated evidence shows that nose-to-brain drug delivery may be an excellent carrier for natural compounds. Therefore, we reviewed natural products with potential anti-CRCI, focusing on the signaling pathway of these drugs' anti-CRCI effects, as well as the possibility and prospect of treating CRCI with natural compounds based on noseto-brain drug delivery in the future. In conclusion, this review provides new insights to further explore natural products in the treatment of CRCI.